2015
DOI: 10.1037/xhp0000065
|View full text |Cite
|
Sign up to set email alerts
|

The role of distractors in object substitution masking.

Abstract: In object substitution masking (OSM) a surrounding mask (typically comprising of 4 dots) onsets with a target but lingers after offset; under such conditions, the ability to perceive the target can be significantly reduced. OSM was originally claimed to occur only when a target was not the focus of attention, for instance, when embedded in an array of distractors (Di Lollo, Enns, & Rensink, 2000). It was argued that the distractors influenced the time taken for focal attention to reach the target. Some recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 106 publications
2
18
0
Order By: Relevance
“…Recent studies have now provided definitive evidence that OSM magnitude does not interact with spatial attention demands (Argyropoulos, Gellatly, Pilling, & Carter, 2013;Camp, Pilling, Argyropoulos, & Gellatly, 2015;Filmer, Mattingley, & Dux, 2014). Specifically, these studies have shown that past reports finding a strong link between spatial attention and OSM have been driven by ceiling effects for the smaller distractor set size conditions.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Recent studies have now provided definitive evidence that OSM magnitude does not interact with spatial attention demands (Argyropoulos, Gellatly, Pilling, & Carter, 2013;Camp, Pilling, Argyropoulos, & Gellatly, 2015;Filmer, Mattingley, & Dux, 2014). Specifically, these studies have shown that past reports finding a strong link between spatial attention and OSM have been driven by ceiling effects for the smaller distractor set size conditions.…”
mentioning
confidence: 71%
“…Thus, it is still possible that nonspatial forms of attention could interact with masking. Indeed, manipulations of spatial attention inherently involve potential confounds of crowding (Camp et al, 2015;Vickery, Shim, Chakravarthi, Jiang, & Luedeman, 2009), and spatial uncertainty. Such confounds may interact with masking processes (Camp et al, 2015), and hence complicate the assessment of the role of attention in OSM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the suppression characteristic of object substitution occurs higher up in system than visual crowding (Chakravarthi & Cavanagh, 2009). Others have however found that crowding and OSM do appear to interact in some circumstances (Camp et al, 2015). We suggest that while crowding and OSM have different loci and reflect dissociable underlying mechanisms, crowding can impact on the objectfile formation mechanisms underlying OSM.…”
Section: Discussionmentioning
confidence: 91%
“…While, as flagged earlier, the presence of simultaneous distractors is not a necessary condition for OSM, and there have been absences of interactions between masking and set-size in OSM reported when the items are widely spaced (Argyropoulos et al, 2013;Filmer et al, 2014), when the distractors are sufficiently close to the target to induce crowding, then an interaction between masking magnitude and the number of distractors is obtained (Camp, Pilling, Argyropoulos, & Gellatly, 2015). This interaction between crowding and OSM suggests that there may be at least some overlap in mechanisms; otherwise purely additive effects would be expected.…”
mentioning
confidence: 99%